Association between geriatric nutritional risk index and osteoarthritis in aged person over 60: data from NHANES 2005-2018 - Lu, Hongxu; Chen, Ping; Song, Yaozong; Su, Yila; Tai, Wulan; Xilin, Baoleri (Frontiers in Medicine, 2025)
BackgroundOsteoarthritis (OA), a prevalent age-related degenerative joint disorder, demonstrates significant associations with nutritional status. This study examines the prognostic value of the Geriatric Nutritional Risk Index (GNRI) in OA risk stratification among elderly individuals.MethodsThis retrospective analysis utilized seven NHANES cycles (2005-2018) encompassing geriatric participants (≥ 60 years) possessing complete GNRI measurements and baseline covariates. For comparative cohort balancing, propensity score matching was executed using inverse probability weighting a matched-pairs design, adjusting for age, alcohol consumption, and the Poverty Income Ratio. Multivariable-adjusted weighted logistic regression quantified GNRI-OA associations, with restricted cubic splines (RCS) characterizing nonlinear dynamics. Subgroup analyses were also performed.ResultsThis cross-sectional analysis identified 656 OA cases among 3,120 rigorously screened geriatric participants. Elevated GNRI levels demonstrated a significant association with increased OA risk among geriatric populations, with the correlation remaining robust in sensitivity analyses adjusted for metabolic confounders. Specifically, a GNRI ≥ 123.63 was associated with a higher probability of OA in this population. RCS analysis revealed a significant non-linear relationship (p_non-linear < 0.001) between GNRI and OA risk, particularly among men and non-smokers. Subgroup analyses indicated that males, Hispanic Americans, Non-Hispanic Black people, non-smokers, and those with a low PIR were more sensitive to changes in GNRI.ConclusionElevated GNRI was independently associated with OA prevalence in geriatric populations, demonstrating nutritional status’s pivotal role in degenerative joint pathophysiology. The impact of GNRI on OA risk may differ across demographic subgroups, highlighting the need for personalized approaches in managing OA risk based on nutritional status.